Analisis Pelaksanaan Sistem Pengendalian Intern Pemerintah di Indonesia - Sensia Gibsi Ompusunggu; Roy Valiant Salomo (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
Law Number 1 of 2004 concerning State Treasury regulates the President as the President of Government and regulates the Government's Internal Control System in Indonesia. In 2008, the Government of Indonesia issued Government Regulation Number 60 of 2008 concerning the Government's Internal Control System. The Government Internal Control System (SPIP) implemented in Indonesia was adopted from the internal Control model made by COSO in 1992. SPIP consists of five elements, namely: (1) Control Environment, (2) Strengthening Assessment, (3) Climate Control, (4) Information and communication and (5) Monitoring. Government Regulation Number 60 of 2008 has been approved for 10 years, the regulation applies. However, the policy contained in Government Regulation Number 60 of 2008 has not been implemented in governance in Indonesia. This can be seen from the evaluation of the government's internal control system carried out by the Financial and Development Supervisory Agency until March 2018 which shows the maturity level of the Government Internal Control System which is still far from the target with the development of Institutions still below level 3 or far from level 5 (optimum level) and weaknesses of the Government's Internal Control System found by the Supreme Audit Agency in the 2015-2017 audit..